The Different of Finger Handheld and Deep Breathing Relaxation Techniques Effect on Reducing Heart Rate and Stress Levels in Primary Hypertension Patients - Arif Setyo Upoyo; Agis Taufik (Jurnal Keperawatan Padjadjaran, 2019)
Stress and hypertension have a reciprocal relationship where hypertension can increase stress, and stress will also increase blood pressure. Therefore we need an effort to control stress in patients with hypertension to prevent increasing blood pressure that can cause complications such as congestive heart failure, myocardial infarction, and stroke. The study aimed to determine the difference between finger handheld and deep breathing relaxation techniques to decrease heart rate and stress levels of primary hypertension patients. The research design used a quasi-experimental design. The research was conducted in Kembaran and East Purwokerto District, Banyumas, Indonesia. There were 50 respondents (25 finger handheld relaxation group and 25 respondents in deep breathing relaxation group). Heart rate and stress levels were measured before and after treatment using heart rate (HR) recordings on digital tensimeter and Subjective Units of Distress Scale (SUDS). Data analyzed using a paired t-test and independent t-test.  The results showed there were significant differences in HR and stress levels before and after finger handheld relaxation (p = 0,000). There were significant differences in HR (p = 0.010) and significant levels of stress (p = 0.000) before and after deep breathing relaxation. There was a significant difference in HR (p = 0.02) but there was no significant difference in stress levels (p = 0.23) after treatment (post-test) between those who received finger handheld and deep breathing relaxation techniques. Conclusion: finger handheld and deep breathing relaxation techniques are equally effective in reducing stress levels in primary hypertension patients. Finger handheld relaxation technique is more effective in reducing HR than a deep breathing relaxation technique.